THE EFFECTIVENESS OF USING MIND MAPPING LEARNING MEDIA IN ECONOMICS LESSONS FOR 10TH GRADE STUDENTS AT SMAS MUHAMMADIYAH 1 PONTIANAK - Safitri, Dian Wahyu (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2024)
This study aims to achieve the following objectives: 1) Determine the effectiveness of using Mind Mapping learning media to enhance learning outcomes. 2) Compare the learning outcomes of students using Non-Mind Mapping media with those using Mind Mapping media. 3) Assess the effectiveness of Mind Mapping in improving student learning outcomes. This research follows a quantitative approach with a quasi-experimental design, where two groups (control and experimental) receive different treatments. The sample for this study consists of 64 students from class X IPS in the odd semester of the 2023/2024 academic year. The findings of this research indicate that: 1) The use of Mind Mapping improves learning outcomes in the classroom. 2) There is a significant difference in learning outcomes between the Non-Mind Mapping class and the Mind Mapping class, specifically in the Economics subject. This is supported by the average posttest results of the control group (67.27) and the experimental group (79.83), as well as the Wilcoxon Rank Sum Test which yielded a significance value of 0.000 (smaller than 0.05) at a 5% significance level, leading to the rejection of H0 and acceptance of H1. 3) However, the use of Mind Mapping is found to be less effective in improving learning outcomes in the Economics subject for class X IPS at SMAS Muhammadiyah 1 Pontianak. This is evident from the average N-gain score of 47.33% for the experimental group.